2012
DOI: 10.1371/journal.pone.0042894
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Small Heat Shock Protein Hsp12p from Candida albicans

Abstract: Hsp12p is considered to be a small heat shock protein and conserved among fungal species. To investigate the expression of this heat shock protein in the fungal pathogen Candida albicans we developed an anti-CaHsp12p antibody. We show that this protein is induced during stationary phase growth and under stress conditions including heat shock, osmotic, oxidative and heavy metal stress. Furthermore, we find that CaHsp12p expression is influenced by the quorum sensing molecule farnesol, the change of CO2 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 64 publications
(97 reference statements)
0
22
0
Order By: Relevance
“…Possibly, HSP9 is required for cell-to-cell adhesion in a large structure like a mushroom. This function was suggested by the fact that overexpression of HSP12 in C. albicans significantly enhanced aggregation of cells (Fu et al 2012). We predict that a DHSP9 mutant of Grifola frondosa will display fruiting body hypoplasia.…”
Section: Monitoring Of Hsp9 Expression Levels During Cultivation Processmentioning
confidence: 80%
See 3 more Smart Citations
“…Possibly, HSP9 is required for cell-to-cell adhesion in a large structure like a mushroom. This function was suggested by the fact that overexpression of HSP12 in C. albicans significantly enhanced aggregation of cells (Fu et al 2012). We predict that a DHSP9 mutant of Grifola frondosa will display fruiting body hypoplasia.…”
Section: Monitoring Of Hsp9 Expression Levels During Cultivation Processmentioning
confidence: 80%
“…However, expression of S. cerevisiae HSP12 and S. pombe HSP9 was induced after heat shock of 40 min or 60 min at 37 C (Praekelt and Meacock 1990;Orlandi I et al 1996). Expression of C. albicans HSP12 could be induced after a heat shock of 10 min at 45 C (Fu et al 2012). Analysis of the G. frondosa promoter sequence and gene expression pattern suggested that Gf.HSP9 might not be induced by heat shock alone.…”
Section: The Identification and Isolation Of Hsp9 From Grifola Frondosamentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, six small heat shock proteins (sHsps), that have to form multimeres to bind their client proteins, have been predicted in C. albicans (Mayer et al, 2013a). These include Hsp12 and Hsp21, which are both upregulated under a variety of stress conditions (Fu, De Sordi, & Muhlschlegel, 2012;Mayer, Wilson, & Hube, 2013b;Mayer, Wilson, Jacobsen, Miramon, Slesiona, et al, 2012). In addition, thermal and oxidative stress lead to the intracellular accumulation of trehalose, which can function as a "chemical chaperone" by stabilizing protein folding (Brown, Budge, et al, 2014).…”
Section: The Heat Shock Response and Fungal Morphogenesismentioning
confidence: 99%